Dehydration in the Arctic stratosphere during the THESEO 2000/SOLVE campaigns - Schiller, C.; Bauer, R.; Müller, M.; Oltmans, S.; Ovarlez, H.; Ovarlez, J.; Schreiner, J.; Stroh, F.; Voigt, C.; Vömel, H.; Cairo, F.; Deshler, M. C.; et al. (Journal of Geophysical Research, 2002)
Balloon-borne measurements of H2O, CH4, and H-2 in January and March 2000 show clear evidence for dehydration inside the polar vortex. At 30-50 hPa, total hydrogen is reduced by approximately 0.5 ppmv. This phenomenon is apparent in all five in situ balloon observations of this period; therefore it is probable that dehydration occurred over extended regions and a long period of this winter which was characterized by a well-confined vortex and low stratospheric temperatures. At altitudes below 50 hPa, where dehydration was strongest in previous Arctic observations and in the austral spring, total hydrogen values (2.CH4 +H2O + H-2) were similar to those found in Arctic profiles from other years where there was no dehydration and to those found at midlatitudes. In some of the dehydrated air masses, small solid particles were found whose crystallization might be connected to the earlier formation of ice particles. Back trajectory calculations for the January observations indicate that the probed air masses had experienced temperatures below the ice frost point in a synoptic-scale cold region several days before the observations. Most likely, the air was dehydrated there. In addition, temperatures in these air masses dropped below ice saturation several hours prior to the observations in the lee of the Scandinavian mountain ridge. For the March measurements, no ice saturation was apparent in the recent history of the air masses, again indicating that dehydration in the Arctic winter 1999/2000 was not a local phenomenon.